A Retrospective Study of Demographic, Clinical, and Histopathological Profiles of Cutaneous Tumors - Bintanjoyo, Lunardi; Hidayati, Afif Nurul; Cita Rosita Sigit Prakoeswa; Murtiastutik, Dwi; Bagus Haryo Kusumaputra; Listiawan, Muhammad Yulianto; Irmadita Citrashanty; Maylita Sari (Faculty of Medicine, Universitas Airlangga, 2022)
Background: In 2007, skin cancers were third most common malignancies in Indonesia. However, profile of cutaneous tumors in our institution has not been studied. Purpose: To evaluate profile of cutaneous tumors in Dermatology and Venerology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya, Indonesia. Methods: This is a descriptive retrospective study. Inclusion criteria was new cutaneous tumor patients. Exclusion criteria was incomplete data. Medical record and photograph database from 2019-2020 were assessed for demography, clinical features, histopathological examination and final diagnosis. Results: There were 379 (5,5%) cutaneous tumors among 6896 new patients at Dermatology and Venereology Outpatient Clinic. Overall, there were more female patients (53.7%) and age group of 0-45 years old (70.4%). Cutaneous tumors more commonly presented as papular (50.4%), multiple (56.5%), nonpigmented (58.3%), asymptomatic lesions (62.5%), with time from onset 0-24 months (66.2%) and location on head and face (61.2%). Benign cutaneous tumors showed similar findings. Malignant cutaneous tumors showed differences including predominantly male sex, age above 45 years old, nodular, solitary, pigmented and easily bleeding lesions. Malignant tumors were less common (6.9%). Most common malignant tumor was BCC. Most common benign and overall cutaneous tumor was seborrheic keratosis. Conclusion: Cutaneous tumors presented across gender and ages, showing heterogenous clinical manifestations. Malignant and benign cutaneous tumors showed similarity on time from onset and location of lesions. However, differences were seen in demographic profiles and majority of clinical features. BCC was the most common malignant cutaneous tumors, while seborrheic keratosis was the most common benign and overall cutaneous tumors.